Investigation of relationships between entrepreneurial attitude and business performance in regional comparison - Kasza, Lajos (Észak-magyarországi Stratégiai Füzetek, 2025)
In my study I give an overview of the interrelationships between entrepreneurial attitudes, which have a major impact on the performance, economic and social perception and success of enterprises. In the literature review, I define entrepreneurship as an economic unit as defined by researchers in the field, and I interpret entrepreneurial attitudes, raising the issue that its regional analysis is far from simple, and its interpretation is complicated. I present my independent research on the impact of entrepreneurial attitudes on family entrepreneurship based on the Global Entrepreneurship Monitor (GEM) 2021-2022-2023. I will explain in detail the methodological issues, such as the source of data, the sample of the analysis, formulate research questions, outline my analytical approach and the statistical methods used for the research.